Interpol review of detection and characterization of explosives and explosives residues 2016-2019() - Klapec, Douglas J. (Forensic Sci Int Synerg, 2020)
This review paper covers the forensic-relevant literature for the analysis and detection of explosives and explosives residues from 2016-2019 as a part of the 19(th) Interpol International Forensic Science Managers Symposium. The review papers are also available at the Interpol website at: https://www.interpol.int/Resources/Documents#Publications